Women, work and computerization charting a course to the future - Balka, Ellen 1956-; Smith, Richard (IFIP advances in information and communication technology, 2000)
ELLENBALKA Simon Fraser University ebalka@Sfu. ca 1. INTRODUCTION In developing the call for papers for the 7th International Federation of Information Processors (IFIP) Women, Work and Computerization Conference, we sought to cast our net widely. We wanted to encourage presenters to think broadly about women, work and computerization. Towards this end, the programme committee developed a call for papers that, in its final form, requested paper submissions around four related themes. These are (1) Setting the Course: Taking Stock of Where We Are and Where We're Going; (2) Charting Undiscovered Terrain: Creating Models, Tools and Theories; (3) Navigating the Unknown: Sex, Time, Space and Place, and (4) Taking the Helm: Education and Pedagogy. Our overall conference theme, 'Charting a Course to the Future' was inspired in part by Vancouver's geography, which is both coastal and mountainous. As such, navigation plays an important part in the lives of many as we seek to enjoy our environs. In addition, as the first Women, Work and Computerization conference of the new millennium, we hoped to encourage the broad community of scholars that has made past Women, Work and Computerization conferences a success to actively engage in imagining--and working towards-- a better future for women in relation to computers. The contributions to this volume are both a reflection of the hard work undertaken by many to improve the situation of women in relation to computerization, and a testament to how much work is yet to be done